A crítica textual do novo testamento de Erasmo a Westcott e Hort: uma introdução com fulcro nas discussões sobre tipos textuais - Carvalho, Adriano da Silva (2024)
The original New Testament documents disappeared very early, probably before the end of the first century, as they are not even quoted in the post-apostolic period and are not even mentioned as having been seen by anyone anywhere. The surviving manuscripts that have come down to us are copies of copies. And these copies have many errors. Therefore, textual criticism is used in order to restore the primitive form of the text before the errors and changes produced by the hands and minds of copyists. A Herculean effort has been made to arrive at the form of the text that circulated or was known in the early years of Christianity. Textual critics, for example, raised many hypotheses and theories such as textual types, with the aim of pointing to handwritten copies that could be closer to what was thought to be the first century text. Editions of "Novum Instrumentum Omne" by Erasmus of Rotterdam, which went on sale March 1, 1516, and "The New Testament in the Original Greek (1881)" by Brooke Foss Westcott and Fenton John Anthony Hort" represent the effort of scholars to give the public an edition of the Greek New Testament based on the best and oldest surviving Greek manuscripts. The present research intends to describe the beginning of the textual criticism of the New Testament with emphasis on the edition of the Greek New Testament of Erasmus of Rotterdam, in the researches of the scholars B. F. Westcott and F. J. A. Hort and in the theory of the textual types.